FAKTOR PENYEBAB, FAKTOR PENGHAMBAT, DAN UPAYA PENANGGULANGAN TERHADAP TINDAK PIDANA PERJUDIAN SABUNG AYAM DI WILAYAH HUKUM KEPOLISIAN RESORT KUPANG KOTA - Saekoko, Imri S; Leo, Rudepel Petrus; Djara Dima, Adrianus (Petitum Law Journal, 2023)
The crime of gambling is a form of crime known as a victimless crime because usually the relationship between the perpetrator and the victim does not show any consequences. And as a result of that, the perpetrator feels comfortable with the crime he has committed. At this time, the existence of cockfighting gambling is rife and even the impact is very detrimental to society both from an economic and spiritual perspective. Then the main problems can be formulated (1) What factors are the causes of cockfighting gambling in the jurisdiction of the Kupang City Police Resort. (2) What factors hinder the Police in eradicating the crime of cockfighting gambling in the jurisdiction of the Kupang City Police Resort. (3) What are the efforts of the Police in overcoming the criminal act of cockfighting gambling in the jurisdiction of the Kupang City Police Resort. Based on the results of research conducted by the author, it is known: (1) The factors that cause cockfighting gambling are environmental factors, local customs or cultural factors, weak factors in implementing religion, economic factors, weak law enforcement factors. (2)The factors that hinder the police in eradicating gambling crimes are internal factors and external factors. (3) Efforts to deal with the crime of cockfighting gambling in Kupang City are preventive and repressive efforts (investigation and arrest of perpetrators).